Unveiling the microbial influence: bacteria’s dual role in tumor metastasis - Lin, Liying; Zhang, Dongyan (Frontiers in Oncology, 2025)
As cancer research advances, the intricate relationship between the microbiome and cancer is gaining heightened recognition, especially concerning tumor metastasis, where bacterial involvement becomes increasingly complex. This review seeks to systematically examine the dual roles of bacteria in the tumor metastasis process, encompassing both mechanisms that facilitate metastasis and the inhibitory effects exerted by specific microorganisms. We explore the mechanisms through which bacteria influence tumor cell migration by inducing chronic inflammation, evading host immune responses, and remodeling the ECM. Moreover, the immunomodulatory potential of probiotics and genetically engineered bacteria offers promising prospects for the prevention and treatment of tumor metastasis. This article elucidates the complexity and emerging frontiers of bacterial involvement in tumor metastasis by examining the clinical significance of bacteria as potential biomarkers and evaluating the effects of antibiotic usage on the metastatic process. We posit that comprehending the biological characteristics and clinical significance of bacteria, as a critical component of the tumor microenvironment, will offer innovative strategies and theoretical foundations for cancer treatment. Furthermore, this article explores future research directions, including the application of microbiome technologies and bacteria-based therapeutic strategies, thereby offering a valuable perspective for the development of novel anti-cancer approaches.